Case report: Electrocardiographic changes in pembrolizumab-induced fatal myocarditis - Nishiyama, Kazuhiro; Morikawa, Kei; Shinozaki, Yusuke; Ueno, Junko; Tanaka, Satoshi; Tsuruoka, Hajime; Azagami, Shinya; Ishida, Atsuko; Yanagisawa, Nobuyuki; Akashi, Yoshihiro J.; Mineshita, Masamichi (Frontiers in Immunology, 2023)
Immune checkpoint inhibitor (ICI)-induced myocarditis is rare but fatal. Because of the rapid course of ICI-induced myocarditis, understanding of clinical course is only possible through information from case reports. We report a case of pembrolizumab-induced myocarditis in which we were able to document the course of electrocardiographic changes from onset to death. A 58-year-old woman with stage Ⅳ lung adenocarcinoma, who had completed her first cycle of pembrolizumab, carboplatin, and pemetrexed, was admitted with pericardial effusion. She underwent pericardiocentesis after admission. A second cycle of chemotherapy was administered 3 weeks after the first cycle. Twenty-two days after admission, she developed a mild sore throat and tested positive for SARS-CoV-2 antigen. She was diagnosed with mild coronavirus disease 2019 (COVID-19), isolated, and treated with sotrovimab. Thirty-two days after admission, an electrocardiogram showed monomorphic ventricular tachycardia (VT). Suspecting myocarditis caused by pembrolizumab, the patient was started on daily methylprednisolone after coronary angiography and endocardial biopsy. Eight days after the start of methylprednisolone administration, she was considered to have passed the acute stage. However, four days later, R-on-T phenomenon triggered polymorphic VT and she died. The impact of viral infections such as COVID-19 on patients be treated with immune checkpoint inhibitors is still unknown and we need to be careful with systemic management after viral infections.